The Perception of Educated People with Different Ethnic Groups towards Exogamy - Siregar, Jumaini; Perangin-angin, Alemina Br (Tradition and Modernity of Humanity, 2021)
Exogamy is the act of marrying someone from another tribe, clan, or similar social unit. This study is about the perception of educated people of different ages and different ethnic groups regarding exogamy. Thus, this paper analyzes the view of educated people in North Sumatera towards intermarriage, either they agree or disagree with exogamy. And then to elaborate the reasons why educated people in North Sumatera agree or disagree with exogamy. The research was conducted by using qualitative research. To answer the problems of the study, the data were collected by giving a questionnaire. The result of this study was the following; (1) Exogamy is supported by the educated people in North Sumatera; (2) The reasons why educated people support exogamy: (1). Exogamy enables educated people to understand other clans and enhance cultural traditions; (2) Adding new family members from various clans to make the family more diverse; (3) It's a normal phenomenon these days; (4) It is unique, interesting and allows educated individuals to reconcile the differences and appreciate their couple's tradition; (5) Exogamy has the potential to push clan growth, and; (6) It is acceptable as long as both families agree.